Relationship between paramacular thinning, cerebral vasculopathy, and hematological risk factors in sickle cell disease - Orssaud, Christophe; Flamarion, Edouard; Michon, Adrien; Ranque, Brigitte; Arlet, Jean Benoit (Frontiers in Medicine, 2023)
Purpose: To look for risk factors for sickle cell maculopathy due to the hematological parameters (especially anemia and hemolysis) or the cerebral vasculopathy.Methods: This retrospective study was conducted on a Referral Center. This Follow-up included optical coherent tomography / optical coherent tomography angiography, a neuroradiological imaging and a hematological assessment (hemoglobin, hemoglobin S level, reticulocytes, mean corpuscular volume, bilirubin and lactate dehydrogenase).Results: Hundred and thirty-two sickle cell patients were included. Maculopathy was observed in 117 eyes of SS patients and 10 eyes of SC patients (p < 0.001), unrelated to a peripheral retinopathy. Cerebral vasculopathy was more frequent in SS patients (p < 0.001), in presence of maculopathy (p = 0.049) and was related to peripheral retinopathy (p < 0.001).All biological parameter significantly differ according to the genotype but not to the existence of cerebral vasculopathy or maculopathy. In a multivariate analysis, reticulocytes and bilirubin were related to the presence of maculopathy and cerebral vasculopathy.Those data's were consistent with the role of anemia or hemolysis markers on cerebral vasculopathy and macular involvement. Since a trend of hemolysis appears as a risk factor for these complications, this validates the preventive plasmapheresis in those patients.